DESIGN OF A COMPACT WIDEBAND BI-DIRECTIONAL PATTERN ANTENNA FOR 5G APPLICATIONS - Lamultree, Suthasinee; Srisukhot, Supada; Saetiaw, Charinsak; Nuangwongsa, Kanawat; Phongcharoenpanich, Chuwong (My University, 2023)
In this research, a wideband bi-directional pattern antenna implemented by a circular monopole encircled with an en-forced-radiation circular ring incorporated with inversed L-shaped stub is designed to operate over the mid-band of 5G applications ranging from 2 to 6 GHz. It is contrived of a copper overlaid on FR4 substrate with relative permittivity of 4.3 and height of 1.6 mm. This proposed antenna is fed by a 50-ohm coplanar waveguide, which is printed on the same side of the radiated circular monopole. To further enrich the impedance matching, a pair of etched slots is added-on the ground plane near the fed line to reduce the return loss. In the study, the initial parameters are theoretically worked out, and then simulation is then performed by using an electromag-netic solutions tool to numerically discover the set of solution parameters. From the simulation results, this proposed antenna offers the |S11| < –10 dB covered the operating frequency running from 1.79 to over 8 GHz with fractional bandwidth 126.90 % and 1.74 to 7.07 GHz with fractional bandwidth 101.04 % for the simulation excluded and included SMA, respectively. It provides a linear polarization with total efficiency better than 81.5 %. After that, an antenna prototype with compact dimensions of 45×45×0.6 mm3 was fabricated and testified to validate the simulation results. The measurement results provide a stability bi-directional pattern with peak gain of 5.54 dBi covering a 10 dB return loss bandwidth of 118.5 % (1.93–7.54 GHz). Simulated |S11|, 2D radiation pattern and gain are reasonably in good agreement with experimental results. Furthermore, this proposed antenna is compared with the current compact, wideband and 5G antenna to indicate its prospective for the interested bands.
Keywords: 5G applications; bi-directional pattern antenna; circular monopole antenna; compact antenna; wideband antenna